2000
DOI: 10.1128/cdli.7.1.6-8.2000
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Responses during Acute Human Granulocytic Ehrlichiosis

Abstract: Human granulocytic ehrlichiosis (HGE) is caused by obligate intracellular bacteria in the Ehrlichia phagocytophila group. The disease ranges from subclinical to fatal. We speculated that cell-mediated immunity would be important for recovery from and potentially in the clinical manifestations of HGE; thus, serum tumor necrosis factor alpha (TNF-␣), interleukin 1␤ (IL-1␤), gamma interferon (IFN-␥), IL-10, and IL-4 concentrations were studied. IFN-␥ (1,035 ؎ 235 pg/ml [mean ؎ standard error of the mean]) and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 14 publications
5
47
0
Order By: Relevance
“…However, it is likely that the extent of CD11b/CD18 activation and its role in aoHGE clearance is partially dependent on IFN-␥. This is consistent with other reports of the dominant role of IFN-␥ in controlling HGE infection (Akkoyunlu and Fikrig, 2000;Dumler et al, 2000;Martin et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…However, it is likely that the extent of CD11b/CD18 activation and its role in aoHGE clearance is partially dependent on IFN-␥. This is consistent with other reports of the dominant role of IFN-␥ in controlling HGE infection (Akkoyunlu and Fikrig, 2000;Dumler et al, 2000;Martin et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…Coinfection of C3H mice with B. burgdorferi and A. phagocytophila was reported to increase the levels of A. phagocytophila and elevate IL-6 levels in the sera at 2 weeks postinfection beyond those of infection with B. burgdorferi alone (35). One report observed that in sera of acute-phase patients, the levels of IL-1␤, TNF-␣, and IL-6 are not elevated (9). Since, unlike those of experimentally infected animals, it is difficult to preserve these rapid-turnover cytokines in the specimens of human patients (5), it is premature to dismiss the role these cytokines play in HGE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute-phase HGE patient sera contain significantly higher levels of IFN-␥ than convalescent-phase sera (9). A. phagocytophila can transiently establish infection in C3H mice without any clinical signs, and these mice develop significant IFN-␥ levels in serum during days 2 to 8 postintraperitoneal inoculation with A. phagocytophila-containing blood from infected SCID mice (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated concentrations of the cytokines gamma interferon (IFN-␥) and interleukin-10 (IL-10) in the serum are seen in patients infected with A. phagocytophilum (6). Our patient displayed another pattern of cytokines in the serum: levels of IL-8 (100 pg/ml; reference geometric mean [GM], 7.5 pg/ml; 95% confidence interval [CI], 6.7 to 8.3 pg/ml), IL-6 (41 pg/ml; reference GM, 2.0 pg/ml; CI, 1.8 to 2.2 pg/ml), IL-10 (19 pg/ml; reference GM, 0.64 pg/ml; CI, 0.42 to 1.0 pg/ml), IL-1␤ (4.2 pg/ml; reference GM, 2.4 pg/ml; CI, 2.3 to 2.6 pg/ml), IFN-␥ (2.6 pg/ml; reference, 1.8 Ϯ 0 pg/ml), and tumor necrosis factor alpha (TNF-␣; 1.7 pg/ml; reference GM, 1.1 pg/ml; CI, 0.90 to 1.3 pg/ml) were determined using a flow cytometry-based cytokine bead array system (Becton Dickinson).…”
Section: Vol 48 2010 Case Reports 1957mentioning
confidence: 99%